Zé Careca e Dona Zene do mercado municipal: as narrativas cruzadas e o imaginário popular de Aracaju - Barreto, Roberta Dayne de Oliveira Couto (2024)
The cultural significance of the Municipal Market of Aracaju for residents of Sergipe is undeniable. Therefore, the access to materials depicting its historiography and its main transformations is extensive. However, there is a noticeable scarcity of records when it comes to highlighting the history of characters who are essential for the dynamism of this environment, as is the case with popular figures like "Zé Careca" and "Dona Zene," the longest-standing selling couple in the Market. My goal is to analyze the importance of these personalities for the history of the Market through their narratives as commercial pioneers of craftsmanship and key historical representatives. This motivation stems from two specific questions: the first relates to the memories of the couple, a factor contributing to the history of the Municipal Market; and the second concerns the reasons that foster their sense of belonging to this place. To achieve this, I recognize the necessity to delve into the categories of memory, identity, place, and popular culture. To collect data, I intend to bolster the investigation through interviews – a technique that underscores the significance of oral history, documentary research, and systematic observation. Once collected, the data will be analyzed using the Discourse Analysis method. Such a perspective will assist me in comprehending the development of the imaginative constructs of these characters, both in terms of their significance to the space and the significance of the space to them. Through this research, I aspire to document the importance of the knowledge held by Zé Careca and Dona Zene as a means of appreciating these personalities for the Market and for the popular culture of Aracaju.